Research on technological properties of potato cellulose for bread production - Sylchuk, Tetiana; Nazar, Mariana; Holikova, Tatiana (My University, 2016)
The problem of deficiency of food fibers in food rations leads to the necessity of searching new sources of ballast compounds. One of the perspective ways of solving this problem is the use of potato cellulose to fortify by food fibers daily used products such as bread and bakery products. Potato cellulose is a high dispersive and contains a high amount of food fibers. Water absorption of potato cellulose has been investigated as well as its effect on the quality of dough and bread. Potato cellulose has water absorption between 1.5 … 2 times higher than in wheat bran thus giving the possibility of making ready products of proper quality. The effect of food cellulose addition to the gluten content in dough has been presented. The expediency of potato cellulose used to enrich ready bread products has been proven.
Keywords: wheat flour; potato cellulose; bread; food fibers; пшеничная мука; картофельная клетчатка; пищевые волокна; хлеб; пшеничне борошно; картопляна клітковина; харчові волокна; хліб; кафедра готельно-ресторанної справи